Strengthening Digital Competence of Elementary School Teachers and Students through Technology Education and Training Activities in Ponco Kresno Village, Negeri Katon District, Pesawaran Regency - Sri Rahayu; Zuriana; Helmita; Rizky Mupty; M Saputra; Linda Septarina; Anggawidia Wibaselppa (Society : Jurnal Pengabdian Masyarakat, 2026)
The transformation of children's education through the utilization of information technology has become a significant phenomenon in the development of education in the digital era. The lack of technological understanding and the limited information technology instruction provided by schools represent increasingly pressing issues in this digital age. In an environment where technology is progressively integrated into daily life, children with limited technological knowledge may face disparities in access to information, educational opportunities, and the capacity to participate in an increasingly digitally connected society. To address this, it is essential to enhance digital competencies for both teachers and students through educational programs and technology training.  The implementation methods used in this activity are the lecture method for delivering basic concepts and information technology theory, the demonstration method to show the operation of applications directly, and the hands-on practice method. The results of the activity indicate a significant improvement in digital competence, both in terms of theoretical knowledge and practical skills in operating software and utilizing technology for learning and self-development needs.